Peran Tokoh Masyarakat dalam Membangun Modal Sosial Pasca Bencana Banjir di Dusun Tempean, Kabupaten Jember - Ely Agustin Purwantoe Saputrie; Dhea Juwita Putri Dhesma Wardani; Sukma Ngesti Arianingsih; Adinda Fathiyatul Hakim; Reva Rizky Hardanti; Joko Mulyono; Mukhammad Handy Dwi Wijaya (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Flooding is one of the most frequent disasters in Jember Regency and has physical, social, and economic impacts on the community. Tempean Hamlet, Rambipuji Subdistrict, is a flood-prone area, causing the community to face various challenges in the post-disaster recovery process. Under these circumstances, community leaders play a crucial role in mobilizing the community’s social resources. This study aims to analyze the role of community leaders in building social capital following the flood disaster in Tempean Hamlet, Jember Regency. The study employs a qualitative method with an ethnographic approach. Informants were selected through purposive sampling and included the hamlet head (who also serves as the chair of Destana), the neighborhood unit (RT) chair, and residents affected by the flood. Data were collected through observation, in-depth interviews, and documentation, and were subsequently analyzed using qualitative data analysis techniques. The results indicate that community leaders play a role in coordinating residents, disseminating information, serving as a bridge between the community and external parties, and encouraging participation in mutual aid activities and environmental restoration. These roles strengthen social capital, characterized by high levels of trust, strong social networks, solidarity, and cooperation among residents. Social capital, formed through daily social interactions, serves as a collective resource that supports the community’s recovery process following a disaster. This study demonstrates that strengthening social capital through the active roles of community leaders can enhance the community’s capacity and resilience in facing and recovering from the impacts of flood disasters.